ヒンパツ スル ナンキョク リュツォ・ホルム ワン ノ カイヒョウ リュウシュツ 1980ネン ～ 2003ネン ノ カイヒョウ ジョウキョウ カラ - 牛尾, 収輝; ウシオ, シュウキ; Ushio, Shuki (2003)
P(論文) 南極リュツォ・ホルム湾で発生した海氷流出の事例を,1980年から2003年までの間について調べた.事例によって流出の面積や持続期間に差異はあるが,過去24年間の内,計19年で流出が認められた.大半の流出が湾の中央北部から東部に至る,ほぼ同一箇所で発生しており,流出は秋季に始まることが多い.1997年厳寒期に発生した広域流出は,翌1998年冬季まで継続し,流出面積・期間共に最大規模となった.その後,2003年までの間は秋季から初冬に亘る流出が毎年継続している.頻発している海氷流出の要因について,南寄りの風,少雪年の継続,暖冬の影響との関連から考察した. The history of sea-ice breakup in Lutzow-Holmbukta, Antarctica, has been investigated for the period 1980-2003. Though spatial and temporal scales for breakups are different among each event, breakup phenomena have occurred at least 19 times. The geographical sites of breakups are almost the same in the bay and commencement is usually in autumn. In particular, the 1997/1998 event covered a wide area and was of long duration. Since then, autumn to early winter breakup has continued until winter 2003. It is suggested that a southerly wind field, small snow depth and mild winter prior to the breakup are factors which favor breakup events. departmental bulletin paper